Perceptions of acceptability and utility of microbicides in Ghana, West Africa: A qualitative, exploratory study - Amanda E Tanner (Taylor & Francis Group, 2008)
Vaginal microbicides, substances that may substantially decrease transmission of sexually transmitted infections (STI) including human immunodeficiency virus (HIV), are currently in clinical trials. They are being presented as woman-initiated prevention methods that have the potential to be used without partners' knowledge. However, it is recognised that covert use may be challenging, due to the accompanying increase in vaginal lubrication. This study explored factors that may influence acceptability and utilisation of vaginal microbicides in Ghana, a sub-Saharan West African country with relatively low rates of HIV.Qualitative research methods were employed in Accra, Ghana in 2005. Individual interviews were conducted with 10 staff working in reproductive health settings, and two focus groups were conducted with young women aged 24-28. Three main topics emerged during the interviews and focus groups, including issues related to available contraceptive and prevention methods, perceptions of microbicide interest and acceptability, and cultural influences on microbicide acceptability and use. Participants discussed issues associated with available contraceptive options that may influence microbicide uptake. All respondents suggested that Ghanaian women would have a high level of interest in microbicides, with varying interest in formulas with different contraceptive and disease prevention properties. Cultural factors that may impact on microbicide use, often related to gender and power issues, were also discussed. Thus, as microbicides are being developed, cultural issues and behavioral correlates will need to be assessed to help ensure acceptability and use. In addition, gendered negotiation power and the implications of covert use need to be addressed in microbicide education and social marketing.